'Mindful teaching': a construct for developing awareness and compassion. Issue 5 (2nd September 2020) - Schussler, Deborah L.
ABSTRACT: The increasing demands of teaching coupled with the erosion of a sense of professionalism has likely contributed to teachers' elevated instances of burnout and loss of well-being. The purpose of this article is to propose a construct of 'Mindful Teaching' as a means to mitigate burnout and improve teachers' well-being and efficacy. Theoretical and empirical research provide the foundation for the Mindful Teaching construct. Mindful teaching includes teachers' awareness and compassion that are both inwardly and externally focused. Mindful teaching can be incorporated into teacher education as a means of helping teachers reflect on and navigate the tensions inherent in their work. Excerpts from a student teacher's journal demonstrate how teacher educators can use the Mindful Teaching construct to improve teacher candidates' well-being by reconnecting them to their sense of purpose through awareness, compassion, improved efficacy, and mindful action.